Upaya Mengurangi Kecemasan Mahasiswa dengan Penerapan Teknik Butterfly Hug - Ayu Dekawaty (Jurnal Medika: Medika, 2026)
Emotional instability in students can lead to anxiety, reflecting an inability to face existing challenges. The resulting anxiety is usually related to the development of increasingly complex thinking skills. At a severe level, anxiety can lead to behavioral emergencies, such as feelings of threat and surprise at new stimuli, a very narrow perceptual field, and even a more severe level of panic. During this phase, feelings of helplessness, aggression or withdrawal, a completely closed perception, and an inability to respond to stimuli will emerge. Efforts to reduce anxiety can be carried out through pharmacological and non-pharmacological therapies. One non-pharmacological technique that can be used is the butterfly hug technique. This community service program aims to prevent behavioral emergencies in students. Community service was carried out by providing an intervention in the form of applying the Butterfly Hug technique to 42 students, with results showing a difference in the average score before and after the intervention. The average anxiety score before the intervention was 17.93 and decreased to 7.98 after the intervention. The output of this community service program is expected to serve as a reference in providing interventions for students' psychosocial problems.